2014
DOI: 10.3390/ijms15058667
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways in Cartilage Repair

Abstract: In adult healthy cartilage, chondrocytes are in a quiescent phase characterized by a fine balance between anabolic and catabolic activities. In ageing, degenerative joint diseases and traumatic injuries of cartilage, a loss of homeostatic conditions and an up-regulation of catabolic pathways occur. Since cartilage differentiation and maintenance of homeostasis are finely tuned by a complex network of signaling molecules and biophysical factors, shedding light on these mechanisms appears to be extremely relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 247 publications
(254 reference statements)
1
129
0
3
Order By: Relevance
“…It is difficult to explain which exact mechanism is responsible for maintaining cartilage tissue content and properties in case of separation of bone and cartilage tissues and using tissue-specific medium. It has been shown before that cartilage homeostasis and function strongly depend on the crosstalk between cartilage and bone (Mariani et al, 2014). It is likely that cartilage and bone cells perform optimally when they receive the specific factors they require for their metabolism, which in turn can lead to positive signaling between the two tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain which exact mechanism is responsible for maintaining cartilage tissue content and properties in case of separation of bone and cartilage tissues and using tissue-specific medium. It has been shown before that cartilage homeostasis and function strongly depend on the crosstalk between cartilage and bone (Mariani et al, 2014). It is likely that cartilage and bone cells perform optimally when they receive the specific factors they require for their metabolism, which in turn can lead to positive signaling between the two tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic response is mainly mediated by hypoxia inducible factors (HIF) ‐1α and HIF‐2α in chondrocyte development. HIF‐1a, is reported to promote chondrogenesis of MSCs, in part by activating SOX9 . The chondrogenic and anti‐catabolic effect of hypoxia could be blocked by HIF‐1α inhibitor .…”
mentioning
confidence: 99%
“…In our study, we analyzed a group of proteins that are potentially found in the medium and have a potential to be beneficial in cartilage repair. The growth, development, maintenance, and improvement of articular cartilages are strictly regulated by multiple signaling pathways performed by several bioactive factors [11]. TGF-β1 is an especially significant factor in the chondrogenic differentiation of MSCs.…”
Section: Resultsmentioning
confidence: 99%